2022
DOI: 10.1136/ijgc-2021-002466
|View full text |Cite
|
Sign up to set email alerts
|

Role of stereotactic body radiotherapy in gynecologic radiation oncology

Abstract: Stereotactic body radiotherapy (SBRT, also referred to as stereotactic ablative radiotherapy (SABR)) has been used in the treatment of primary and metastatic solid tumors, and increasingly so in gynecologic oncology. This review article aims to summarize the current literature describing the utility of SBRT in the primary, recurrent, and limited metastatic settings for gynecologic malignancies. The use of SBRT in both retrospective and prospective reports has been associated with adequate control of the treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…IGBT using 3D images for RT planning allows for more precise and individualized treatment compared even to stereotactic body radiotherapy (SBRT) [23][24] . However, modern IGBT procedures with increasing real-time steps and complexities will require for more technical and manpower resources before con dent applications.…”
Section: Discussionmentioning
confidence: 99%
“…IGBT using 3D images for RT planning allows for more precise and individualized treatment compared even to stereotactic body radiotherapy (SBRT) [23][24] . However, modern IGBT procedures with increasing real-time steps and complexities will require for more technical and manpower resources before con dent applications.…”
Section: Discussionmentioning
confidence: 99%
“…SBRT is widely used for the treatment of a wide variety of other primary and metastatic cancers. [1][2][3][4] In particular,for pelvic lymph node (LN) oligometastases,one-year local control of 74% 5 or higher 6 can be achieved with a mild risk of toxicities. For the clinical performance of SBRT, dedicated systems and regular clinical linear accelerators (Linacs) are employed.…”
Section: Introductionmentioning
confidence: 99%
“…This results in a high biologically effective dose within the target and rapidly falling off doses away from the target, potentially maximizing tumor control and minimizing normal tissue damage. SBRT is widely used for the treatment of a wide variety of other primary and metastatic cancers 1–4 . In particular, for pelvic lymph node (LN) oligometastases, one‐year local control of 74% 5 or higher 6 can be achieved with a mild risk of toxicities.…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews reported promising results in terms of local control and survival regarding use of SBRT in recurrent gynaecological cancer [38,39].…”
Section: Introductionmentioning
confidence: 99%